Inspiring next generation of engineers through service-learning robotics outreach and mentorship programme. (7th October 2016) - Ilori, Olusoji; Watchorn, Andrew
This article describes the organization of a service-learning robotics outreach and mentorship programme in an engineering department of a developing country. The programme is designed to tackle the problem of lack of integrative courses in engineering programmes and the lack of interest in science technology engineering and mathematics subjects among primary and secondary school students. Under the programme, a robotic team is formed consisting of undergraduate engineering students as mentors/coaches and primary and secondary school students as team members. The team members are taught how to design, build, and program robots to solve challenges by their mentors. The programme is intended to foster creative problem-solving abilities of students in science technology engineering and mathematics subjects at all levels of education in the context of a resource-constrained teaching and learning environment. The impacts of the programme are also reported.